Toughening mechanism of carbon fibre-reinforced polymer laminates containing inkjet-printed poly(methyl methacrylate) microphases. (May 2018) - Zhang, Yi; Stringer, Jonathan; Hodzic, Alma; Smith, Patrick J
It has previously been demonstrated that inkjet-printed thermoplastic microphases are capable of producing a significant increase in mode I interlaminar fracture toughness ( G Ic ) in carbon fibre-reinforced polymer with no significant reduction in other mechanical properties or increase in parasitic weight. In this work, the evolution of the microphase structure during processing and how this is influenced by the chosen printing parameters were investigated. Samples were prepared that enabled monitoring of the microphases during all steps of fabrication, with the thermoplastic polymer found to form a discrete spherical shape due to surface energy minimisation. Based upon the morphology and properties of the thermoplastic microphases, it was hypothesised that the increased toughness was due to a combination of crack deflection and plastic deformation of the microphases. Samples were produced for the double cantilever beam fracture toughness testing using the same printing conditions, and both G Ic values and scanning electron microscopy of the fracture surface supported the proposed hypothesis. The feasibility of selective toughening is also demonstrated, which presents potential to tailor the mechanical properties of the carbon fibre-reinforced polymer spatially.